Durvalumab Plus Olaparib in Previously Untreated, Platinum-Ineligible Patients With Metastatic Urothelial Carcinoma: A Multicenter, Randomized, Phase II Trial (BAYOU). Issue 1 (1st January 2023) - Rosenberg, Jonathan E.; Park, Se Hoon; Kozlov, Vadim; Dao, Tu V.; Castellano, Daniel; Li, Jian-Ri; Mukherjee, Som D.; Howells, Kathryn; Dry, Hannah; Lanasa, Mark C.; Stewart, Ross; Bajorin, Dean F.
Abstract : PURPOSE: Homologous recombination repair gene mutations (HRRm) are common in urothelial carcinoma (UC), rendering tumor cells sensitive to poly (ADP-ribose) polymerase (PARP) inhibition. We assessed efficacy and safety of durvalumab (anti–programmed cell death ligand-1) plus olaparib (PARP inhibitor) in patients with metastatic UC (mUC). METHODS: This randomized, multicenter, double-blind, phase II trial enrolled untreated, platinum-ineligible patients with mUC. Patients (N = 154) were randomly assigned 1:1 to receive durvalumab (1, 500 mg intravenously once every 4 weeks) plus olaparib (300 mg orally, twice daily) or durvalumab plus placebo. The primary end point was progression-free survival (PFS) assessed by investigators per RECIST version 1.1. Secondary end points included overall survival in all patients and PFS in patients with HRRm. RESULTS: Overall, median PFS was 4.2 months (95% CI, 3.6 to 5.6) for durvalumab plus olaparib and 3.5 months (95% CI, 1.9 to 5.1) for durvalumab plus placebo (hazard ratio [HR], 0.94; 95% CI, 0.64 to 1.39; log-rank P value, .789). Median overall survival was 10.2 months (95% CI, 7.0 to 13.9) and 10.7 months (95% CI, 7.2 to 17.3), respectively (HR, 1.07; 95% CI, 0.72 to 1.61). In the 20% of patients with HRRm, median PFS was 5.6 months (95% CI, 1.9 to 8.1) and 1.8 months (95% CI, 1.7 to 2.2), respectively (HR, 0.18; 95% CI, 0.06 to 0.47). Treatment-related grade 3 or 4 adverse events occurred in 18% and 9% of patients, respectively. CONCLUSION: Adding olaparib to durvalumab did not improve survival outcomes in an unselected mUC population. Efficacy outcomes with durvalumab were similar to those reported for other anti–programmed cell death-1/programmed cell death ligand-1 agents. However, the results of secondary analyses suggest a potential role for PARP inhibition in patients with UC harboring HRRm.